Carbon in airway macrophages from children with asthma. Issue 7 (24th February 2014) - Brugha, Rossa E; Mushtaq, Naseem; Round, Thomas; Gadhvi, Dev H; Dundas, Isobel; Gaillard, Erol; Koh, Lee; Fleming, Louise J; Lewis, Daniel J; Sanak, Marek; Wood, Helen E; Barratt, Benjamin; et al.
Abstract : Background: Airway macrophage (AM) phagocytosis is impaired in severe asthma. Prostaglandin (PG) E2 and D2 are increased in severe asthma and suppress AM phagocytic function in vitro. In this study, we sought evidence for PG-mediated impairment of phagocytosis of inhalable carbonaceous particulate matter (PM) by AM in children with severe asthma compared with mild asthmatics and healthy controls. Methods: AM were obtained from children with asthma and healthy controls using induced sputum. AM carbon area (μm 2 ) was assessed by image analysis. In a subgroup of asthmatics, urinary PGE2 and PGD2 metabolites were measured by high-performance liquid chromatography, and PM exposure at the home address was modelled. Phagocytosis of PM by human monocyte-derived macrophages and rat AM was assessed in vitro by image analysis. Results: AM carbon was 51% lower in children with moderate-to-severe asthma (n=36) compared with mild asthmatics (n=12, p<0.01) and healthy controls (n=47, p<0.01). There was no association between modelled PM exposure and AM carbon in 33 asthmatics who had a urine sample, but there was an inverse association between AM carbon and urinary metabolites of PGE2 and D2 (n=33, rs=−0.40, p<0.05, and rs=−0.44, p<0.01). PGE2 10 −6 M, but not PGD2 10 −6 M, suppressed phagocytosis of PM10 by human macrophages in vitro (p<0.05 vs control). PGE2 10 −6 M also suppressed phagocytosis of PM10 by rat AM in vitro (p<0.01 vs control). Conclusions: Phagocytosis of inhaled carbonaceous PM by AMs is impaired in severe asthma. PGE2 may contribute to impaired AM phagocytic function in severe asthma.